Long-term therapeutic outcome of ophthalmic complications following endoscopic sinus surgery. Issue 38 (September 2016) - Wu, Heping; Shen, Tao; Chen, Jingchang; Yan, Jianhua
Abstract : Abstract: Ophthalmic complications associated with endoscopic sinus surgery (ESS) are quite rare. There is a paucity of reliable data and limited experience on the clinical findings and treatments of these injuries. Our study here is to characterize the types of orbital injury following ESS, in particular extraocular muscle injury, and to evaluate the long-term therapeutic outcomes as compiled from a relatively large sample of Chinese patients. A series of 27 patients (21 males and 6 females; mean age = 42.6 years, ranges: 10–60 years) were retrospectively reviewed. The mean duration of orbital complication was 6.6 months (ranges: 1 day to 24 months). The right eye was affected in 19 patients and the left in 8 patients. All patients had various extraocular muscle dysfunction, including contusion, oculomotor nerve damage, muscle entrapment, muscle transection, and muscle destruction. All patients subjected to strabismus surgery showed an obvious reduction in deviation. Three patients achieved orthophoria without any surgery during the period of observation. All patients displayed mild to complicated orbital hemorrhage that often disappeared within 2 weeks. Optic nerve injury occurred in 29.6% of patients and vision damage in these patients was often irreversible. All patients with ophthalmic complications after ESS had strabismus and extraocular muscle dysfunction. Timing and type of strabismus surgery performed depended on the severity and number of muscles involved as well as the type of injury. This surgery is less effective in cases of restriction factor adhesion and/or entrapment as compared to that of patients with other types of strabismus. Orbital hemorrhages were usually resolved spontaneously, but optic nerve injury was mostly irreversible.